Symposium 9: Processes and their Support in a Developing Interdisciplinary Learning Community - Motschnig-Pitrik, Renate; Derntl, Michael; Figl, Kathrin; Kroop, Sylvana; Logar, Sylvia; Mangler, Juergen; Wenninger, Barbara (Proceedings of the International Conference on Networked Learning, 2006)
In this experiential paper we employ action research to investigate the real life processes and technology support in building an interdisciplinary blended learning community in which, at the stage of writing the article, the authors are participating. Regarding technology support, we are interested in the requirements – concerning functionality and usability – for the implementation of web-based support modules for blended communities. Regarding real world processes we explore and reflect on the expectations, significant events, and insights we gained through the participation in our blended community.